2012
DOI: 10.1134/s1063784212050027
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of adenine and uracyl molecules through electron captures in collisions with ions

Abstract: The time of flight mass spectrometry method is used to study processes occurring when 36 keV multiply charged Ar ions (Ar 6+ ) capture electrons from adenine and uracyl molecules. Adenine and uracyl constitute one of two base pairs entering into the RNA composition. The fragmentation scheme of resulting molecular ions is derived by analyzing correlations between the detection times of all fragment ions. Frag mentation patterns for molecular ions resulting from molecule ionization by photons, electrons, protons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…Additionally, one of the isotopic studies also suggested that N7, N9, and C8 (see Fig. 1 66 . Thus, we also considered the following reaction in which an intact neutral fragment is the byproduct:…”
Section: Major Electron-induced Cationic Fragments From Adeninementioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, one of the isotopic studies also suggested that N7, N9, and C8 (see Fig. 1 66 . Thus, we also considered the following reaction in which an intact neutral fragment is the byproduct:…”
Section: Major Electron-induced Cationic Fragments From Adeninementioning
confidence: 92%
“…A recent study by Afrosimov et al suggests that the C 3 H 3 N 3 + at m/z 81 is not formed from the loss of two HCN groups but rather from the loss of the neutral fragment, C 2 H 2 N 2 , from the parent adenine, which they suggest is the more favorable pathway. 69 Thus, we also considered the following reaction in which an intact neutral fragment is the byproduct:…”
Section: Major Electron-induced Cationic Fragments Of Adeninementioning
confidence: 99%
“…38,39 The CID processes of protonated purines 40−42 and purine cations 43 have been thoroughly explored. Other purine fragmentation experiments have focused on electron, 44,45 photon, 46 ion, 47,48 and atom 49 bombardment to achieve molecular dissociation. Several of these studies report the sequential loss of HCN molecules from adenine species, lending support to an HCN precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Tandem mass spectrometry involving collision-induced dissociation (CID) paired with theoretical calculations can reveal underlying mechanisms and important precursor molecules to specific syntheses. , The CID processes of protonated purines and purine cations have been thoroughly explored. Other purine fragmentation experiments have focused on electron, , photon, ion, , and atom bombardment to achieve molecular dissociation. Several of these studies report the sequential loss of HCN molecules from adenine species, lending support to an HCN precursor .…”
Section: Introductionmentioning
confidence: 99%
“…[15] Some experimental techniques allow the creationofmultiply ionized molecular species in the gas phase:c ore ionization induced by X-ray absorption, [16] electron impact, [17,18] and highly chargedi on collision. [19] As several charges are present in the system,p henomenas uch as Coulomb explosionc an be observed. Our group hasr ecently shown that this explosion can occur in competition with Htransfer within the glycined ication.…”
mentioning
confidence: 98%